Evaluating soundscape intentions in landscape architecture: a study of competition entries for a new cemetery in Järva, Stockholm. Issue 7 (3rd July 2017) - Cerwén, Gunnar; Wingren, Carola; Qviström, Mattias
Abstract : While soundscape is increasingly acknowledged within landscape planning and design discourse, there is little research that clarifies how soundscapes are actually dealt with in landscape architecture practice – partly owing to methodological insufficiencies. This paper, therefore, describes a model for evaluating soundscape treatment in landscape design proposals, focusing on three key aspects. With the dual aim of testing the model, and learning more about how soundscape is approached in practice, the paper spotlights a major design competition for a new cemetery in Sweden. The model proved fruitful and easy to apply. It showed that only limited attention was paid to soundscape in the competition as a whole, and was a useful means of pinpointing proposals where soundscape was fully considered as a design feature; one competition entry that did so is described in the paper. Discussions cover design practice, trends in the competition and model application.